Harnessing Plant Growth-Promoting Rhizobacteria (PGPRs) for Sustainable Management of Rice Blast Disease Caused by Magnaporthe Oryzae: Strategies and Remediation Techniques in Indonesia - Ullah, Qudrat; Munir, Taimoor; Mumtaz, Tayyiba; Chawla, Mahnoor; Amir, Muhammad; Ismail, Muhammad; Qasim, Muhammad; Ghaffar, Aisha; Haidri, Irfan (Indonesian Journal of Agriculture and Environmental Analytics, 2024)
Plant Growth-Promoting Rhizobacteria (PGPRs) are beneficial microorganisms that play a crucial role in sustainable agriculture by enhancing soil fertility, improving nutrient uptake, and promoting plant growth and resilience. In Indonesia, rice (Oryza sativa) stands as a vital staple crop, essential for food security and economic stability. However, rice production faces significant challenges, prominently including rice blast disease caused by the fungal pathogen Magnaporthe oryzae. A systematic literature review is conducted, showing that this disease severely impacts yield and quality, threatening food security in the region. The aim of this review is to explore the potential of PGPRs in managing rice blast disease and enhancing rice production in Indonesia. The scope includes examining the mechanisms of action of PGPRs, presenting case studies on their application, discussing challenges and opportunities for wider adoption, and proposing future research directions to optimize their effectiveness in sustainable rice cultivation.